Ultrasound-assisted extraction of anthocyanin from black rice bran and its encapsulation by complex coacervation - Lourembam Monika Devi; Amit Baran Das; Laxmikant S. Badwaik (Food Hydrocolloids for Health, 2024)
The present work was planned to optimize extraction process of phenolics, flavonoids, monomeric anthocyanin and antioxidants from black rice bran using Ultrasound-assisted extraction and finally utilize it for encapsulation using double emulsion coacervation process. Response surface methodology (RSM) was employed for optimization of extraction process. Acidified ethanol (1 M HCl) was used as extraction solvent and ultrasound power (W) and extraction time (min) were used as independent variables. Face centered composite design (FCCD) data was successfully opted and developed a 2nd order polynomial equation with R2 value of 0.94 for total phenolic content (TPC), 0.95 for total flavonoid content (TFC), 0.87 for 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 0.98 for total anthocyanin content (ANCs) respectively. Kinetic model study for extraction of anthocyanin was compared to conventional extraction process. Characterization of the extracts was performed using high pressure liquid chromatography analysis (HPLC). Cyanidin-3-glucoside is the predominated anthocyanin found as compared to peonidin-3-D-glucoside. Finally, coacervated microcapsules were developed using anthocyanin extract as core solution and gelatin and acacia gum as wall materials. Characterization of the microcapsules in terms of moisture content, hygroscopicity, solubility, encapsulation efficiency and surface morphology were evaluated. The result thus obtained shows that potential anthocyanin content from black rice bran can be utilized as food ingredients for various food application and formulation of functional food.